An early story of Kho Ping Hoo - Watson, C.W. (Wacana, Journal of the Humanities of Indonesia, 2017)
Kho Ping Hoo (1926-1994) is the most well-known of all Indonesian writers of popular silat stories, largely set in China, which describe the adventures and romances of legendary heroes famed for their skill in martial arts. It is less well-known that he began his career writing critical stories about socio-economic conditions in the late 50s and early 60s. This paper discusses one of these stories. It places the story in the context of political developments of the time, in particular as they affected the Chinese Indonesian community. The paper argues that this story and one or two others like it come at the end of a tradition of Sino-Indonesian literature which had flourished from the end of the nineteenth century until the mid-1950s. After 1960, Chinese-Indonesian writers cease writing realist fiction of any kind and write either silat stories or romantic stories set in middle class urban environments.